1992
DOI: 10.1007/bf01741853
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of rat hepatic macrophages by treatment with interleukin-2 and streptococcal preparation OK432, with reference to antitumor activity, soluble factor production and Ia expression

Abstract: The effect of biological response modifiers, such as interleukin-2 (IL-2) and streptococcal preparation OK432, on the functions of hepatic macrophages was investigated. The macrophages, even with no exogenous stimulation, produced superoxide anion (O2-) and tumor necrosis factor (TNF), displayed cytotoxicity against K562 cells and cytostasis against P815 cells and expressed immune-region-associated antigen (Ia). IL-2 administered in vitro or in vivo enhanced O2- production by hepatic macrophages and the intrav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Ogle et al showed that KC's are responsible for the increased levels of TNF-␣ and IL-6 in trauma, hemorrhagic shock, and resuscitation [26,27]. Decreasing the number or functional ability of KC's can lead to decreased levels of inflammatory cytokines, as seen in models of hepatic resection and cecal ligation or puncture [28,29]. We have previously demonstrated that modulation of KC function has a direct effect on cytokine release in rats with superior mesenteric artery occlusion [30].…”
Section: Introductionmentioning
confidence: 98%
“…Ogle et al showed that KC's are responsible for the increased levels of TNF-␣ and IL-6 in trauma, hemorrhagic shock, and resuscitation [26,27]. Decreasing the number or functional ability of KC's can lead to decreased levels of inflammatory cytokines, as seen in models of hepatic resection and cecal ligation or puncture [28,29]. We have previously demonstrated that modulation of KC function has a direct effect on cytokine release in rats with superior mesenteric artery occlusion [30].…”
Section: Introductionmentioning
confidence: 98%
“…It augments the activity of macrophages, lymphocytes and natural killer (NK) cells, 2 and induces multiple cytokines including interleukin (IL)‐1, 3 IL‐2, 3 IL‐6, 4 tumor necrosis factor (TNF)‐α 5 and interferon (IFN)‐γ 6,7 . In clinical studies and animal experiments, OK‐432 has been found to augment these activities in peripheral blood lymphocytes (PBL), 8 pleural effusion lymphocytes, 9 splenic lymphocytes and hepatic macrophages 10,11 . However, it has not been specifically reported in hepatic lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is possible that TNF-a and NOx produced from activated macrophages are interacting to exert the anti-proliferative activity against AH-130 cells. It is known that LPS-or IL-2-activated macrophages secretes superoxide anions that have cytotoxic effect on tumor cells [8,35,36]. To examine the involvement of superoxide anions in the anti-tumor activity against AH-130 cells, we added superoxide dismutase and catalase to coculture of AH-130 cells and LPS-or IL-2-activated peritoneal macrophages.…”
Section: Discussionmentioning
confidence: 99%